Management of Coffee MSMEs at Romban Djoyo Community in the Tourism Village - Nurkhayati, Siti; Shofwan, Imam; Gupta, Sachin (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2024)
Management of MSMEs is crucial as the national economy is supported by the participation of MSMEs from coffee agriculture, tourism, and processing industries, which are able to absorb labor and contribute to GDP growth. However, in the process, MSMEs face classic challenges along with the demands for increased competitiveness and business sustainability. This study aims to describe the management of coffee MSME in the Romban Djoyo community in Central Java Tourism Village. This study is descriptive research with a qualitative approach. Data collection uses observation, interview, and documentation techniques. The research participants were the members of Romban Djoyo community. Data validity with source and technique triangulation. The research results that MSMEs management consists of finance, production, marketing, and human resources. The conclusion of this study is that financial management is carried out through planning and controlled informally, with funding sourced from government assistance and personal funds. Production follows SOPs using tools with raw materials from farmers distributed directly and indirectly, marketing by designing products based on consumer requests and promoted through social media. Human resource management includes mentoring and training. This research classifies the management of MSMEs collectively. The recommendations, expanding access to funding, utilizing digital marketing, strengthening partner network and branding.